Catatan dari luar pagar - Sumarjo, Yakob, 1939- (Bandung : Citra Aditya Bakti, 1994)
Conditions of socio-culture, education, etc. in Indonesia; collected articles.
Keywords: Education -- Indonesia; Indonesia -- Civilization